The changing political culture of the African National Congress. Issue 5 (28th July 2016) - de Jager, Nicola; Steenekamp, Cindy Lee
Abstract : The early elite of the African National Congress (ANC) embraced values of moral improvement, individual responsibility and a sense of social consciousness. The ANC now governs South Africa, but with what appears to be a different set of principles. The current scourge of corruption, increasing state control, coupled with a general lack of service delivery point to behaviour of the ruling party which is inward-looking, self-seeking and self-preserving. Arguing that political culture and its accompanying values and attitudes is a prime motivator of behaviour, the paper seeks to understand the changing political culture of the dominant party. To understand the political culture of the ANC we use interviews with ANC parliamentarians and ANC supporters conducted in 2006–2007 and 2013 as well as an analysis of the ANC's Strategy and Tactics policy documents. We contend that the liberal values of the early elites were never fully embedded, but in their stead is a liberationist culture, where the state is normatively understood to be extensive and embodying the will of the people. We argue, that through the resulting centralized determination of the interests of the people, patronage networks, and diminishing of accountability, a system conducive to corruption and the pursuit of personal interest is created.